ANALYSIS OF QUANTITATIVE EVALUATION PROBLEM OF QUALITY IN HIGHER EDUCATION - Чередниченко, Ольга Юрьевна; Лютенко, Ирина Викторовна (Eastern-European Journal of Enterprise Technologies, 2012)
In the article the existing principles and approaches the quality assessment of various objects and features of education quality are considered, the task of synthesis of quality assessment model for educational systems is set, the choice of network model of complex evaluation is substantiated.